Correlating factors between vertebral fracture and fracture-associated intervertebral disc vacuum phenomenon after thoracolumbar fracture surgery: a single-centre retrospective study - Yao Fang; Yuchao Ye; Qing Wang; Sining Zhang; Guangfeng Ling; Kongning Chen; Hengmei Chen; Wugui Chen; Chengzhao Liu (BMC Musculoskeletal Disorders)
Abstract Study design A retrospective study. Purpose Some studies have found the correlation between traumatic vertebral fractures and intervertebral disc vacuum phenomenon (IVP), but the study about relationship between thoracolumbar fractures and IVP at one year after fracture is lacking. Therefore, the purpose of this study was to analyze the prevalence of fracture-associated IVP (FAVP) in patients with thoracolumbar spine fracture at 1 year postoperatively and discover the related factors. Methods This study included patients admitted to the spine surgery department of a university hospital from January 2016 to December 2021 after traumatic single-segment thoracolumbar fractures. IVP was categorized using computed tomography (CT), and the patient’s gender, age, fracture type, trauma mechanism, 1-year postoperative outcome of the intravertebral shell phenomenon (ISP), degree of vertebral repositioning, and LSC score were recorded. The correlation between each factor and FAVP was analyzed by Pearson’s Chi-square and Student’s t test. Results A total of 236 patients with traumatic single-segment thoracolumbar fractures were included in the study. All patients underwent CT scanning preoperatively, within 3 days postoperatively, and about 1 year postoperatively. 71 patients developed IVP at 1 year postoperatively, of which 47 had FAVP and 24 had degeneration-associated IVP (DAVP). There was a significant correlation between age and both FAVP or DAVP (P < 0.05). There was a significant correlation between fracture type, LSC score, trauma mechanism, and 1-year postoperative outcome after ISP and FAVP (P < 0.05). Conclusion Patients with thoracolumbar fractures have a higher incidence of postoperative FAVP. FAVP is more likely to occur in patients with an enlarged vertebral cavity 1 year after surgery for the ISP. FAVP needs to be taken into consideration when treating patients with high-energy trauma and older burst fractures.